Determinants of nutritional outcome among beneficiaries of Nutrition Rehabilitation Centre - Chauhan, Dhwani N; Chauhan, Naresh T; Patni, Mohamed Anas Mohamed Faruk; Solanki, Pinakini (Indian Journal of Community Health, 2023)
Background: Under Mission Balam Sukham, children of 6 months to 5 years having severe acute malnutrition (SAM) along with complications are managed at Nutrition Rehabilitation Centre (NRC). They are admitted for 14 days with the provision of a nutritional diet and medicines. Objectives: To explore determinants of nutritional outcome of SAM children admitted at NRC Methods: A prospective cohort study was conducted comprising 63 children aged 6 months to 5 years having SAM along with complications admitted at NRC of New Civil Hospital, Surat (NCHS) for 10 months. Results: The majority of participants were boys (54%), 12-23 months of age (50.8%), and Grade III socioeconomic class (39.6%). The duration of stay ranged from 2-36 days. The average duration of stay was 12.78 + 6.49 days; 14.26 ± 5.99 days for boys and 11.10 + 6.73 for girls. 18.8% stayed at NRC for 14 days. The average weight gain was 5.46 g/kg/day. A significant improvement in weight was seen in boys (t=2.20, p<0.05), working mothers (t=2.44, p<0.01), exclusively breastfed children (t=3.62, p<0.01) of 6-11 months, full-term children of 12-23 months (t=4.0, p<0.05). The children of 12-23 months (t=2.90, p<0.01) and boys (t=2.15, p<0.05) showed significant improvement in underweight (WAZ). Wasting improved significantly in age below 36 months (p<0.05). 20.6% could achieve the target weight. Conclusion: NRC is an effective life-saving modality for malnutrition but its outcome is associated with factors like boys, exclusive breastfeeding, and full-term.